Utilization of Quizizz as a Formative Assessment Media in the Interspace Interaction Material - Ilah Armilah (International Journal of Advance Social Sciences and Education (IJASSE), 2023)
Formative assessment using the Quizzizz application can be a formative assessment medium for Interspatial Interaction material in the 7th grade social studies subject. This research took 28 class VII B students at SMP Negeri 4 Bukit Kemuning as research subjects. This research method uses a combination research method (Mixed Methods). The research results showed that digital-based formative assessment, in this case using the Quizizz application, can foster interest and motivation to learn in class VII students at SMP Negeri 4 Bukit Kemuning so that they aspire to get better results in the next assessment. And based on observations during the assessment, students looked enthusiastic.